The Effectiveness of Policyholder Protection in AJB Bumiputera 1992 Medan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study was motivated by a significant increase in the number of complaints against the insurance industry, especially cases of claim default in 2018-2022. The purpose of the study was to measure and analyze the effectiveness of policyholder protection at AJB Bumiputera 1912 Medan through a regulatory effectiveness approach as variable x is the legal factor itself, law enforcement factors, facilities or facilities, community factors, and cultural factors. The research method is descriptive quantitative. Primary data was obtained from questionnaires and interviews. While secondary data is in the form of documentation studies, in the form of Articles of Association, general conditions of the policy, and laws and regulations that support the research. The results of the study on respondents’ responses show that all indicators of factors affecting the achievement of regulatory effectiveness have a fairly high percentage. However, it should be noted that the factors that produce ineffective percentages are 62.45% for law enforcement factors and 60.14% for community factors. Both factors are caused by the late presence of laws that clearly regulate the form of joint ventures, No. 4 of 2023 concerning Development and Strengthening of the Financial Sector (P2SK), where it is stated in article 53 paragraph 2e: “distribution of profits and losses on Joint Venture activities for members”.